India: Shadow WTO agricultural domestic support notifications - Gopinath, Munisamy (International Food Policy Research Institute, 2008)
In this study, we examined India's domestic support policies to understand their classification and measurement for the purposes of official World Trade Organization (WTO) notifications. We then employed the underlying methods to prepare shadow notifications of India's domestic support for 1998-2005. Following that, we explored alternative support-definition scenarios and their possible effects on shadow notifications. Preliminary support estimates for 2006-2007 and a projection for 2015 are also provided with a discussion on how the latest WTO (2008) draft modalities are likely to impact India's domestic support. India's official notifications began in 1995 with green box support of nearly US$2 billion and limited use of special and differential treatment. The product-specific aggregate measure of support (AMS) was negative because external reference prices were larger than minimum support prices. Nonproduct-specific AMS, by way of fertilizer, electricity, irrigation, credit, and seed subsidies, accounted for about 7 percent of the value of agricultural production in 1995. In subsequent notifications, for 1996 and 1997, several key changes were observed. The first was the transfer of 80 percent of fertilizer, irrigation, and electricity subsidies from nonproduct-specific AMS to special and differential treatment of low-income and resource-poor farmers. Product-specific AMS remained negative, but the value of production was replaced by eligible production, which was set equal to quantities procured by public agencies in 1996 and 1997. Shadow notifications, based on our understanding of the underlying methods, showed that green box support had grown to nearly US$8.0 billion in 2005. Estimates of input subsidies to low-income and resource-poor producers declined between 1998 and 2002, but they amounted to about US$4.5 billion or 4 percent of the value of agricultural production in 2005. Product-specific AMS remained negative through 2005 mostly because of the wide gap between external reference prices and minimum support prices. Nonproduct-specific AMS accounted for about 1 percent of the annual value of agricultural production for 1998-2005. Alternative support-definition and measurement scenarios showed a possible increase in product-specific AMS. However, reallocating input subsidies from special and differential treatment to nonproduct-specific AMS would only eliminate some of the slack in the latter's de minimis exemption. With India's general elections expected in early 2009, the immediate future includes popular policies such as credit subsidies and significant growth in minimum support prices. Nevertheless, non-product-specific AMS would not likely exceed the limits proposed in the Doha Round (that is, 10 percent of value of production) even with popular policies. However, product-specific AMS would turn positive, especially in cereals, with high growth in support prices and the appreciation of Rupee as seen in recent years. Projections for 2015 suggest that de minimis exemptions would be about US$16 billion each for product-specific and non-product-specific AMS, giving India ample flexibility in domestic support policies.